Influência da vazão e da posição do jato de água na transferência de oxigênio por tubos venturi - Gianjacomo, Carlos Henrique (2017)
The objective of this work was to evaluate the reoxygenation potential of water using Venturi tubes. The experiments were performed in two tanks: Horizontal (HT) and vertical (VT), with useful volumes of 100 L and 63 L, respectively. The tests followed the statistical design associated with the surface methodology of responses, having as independent variables the water flow (Qwater) and the inlet position of the jet (Pjet), for a single Venturi tube and two associated tubes in parallel. Were determined as response the global oxygen transfer coefficients from air to water (KLa) and oxygenation efficiencies (OE). The results indicate that the water flow significantly influenced the values of KLa and OE, whereas the position of the jet only had effect when the Venturi tubes were associated in parallel, in both tanks. In general, the best KLa results, up to 50 h-1, were obtained for higher water flows and a jet positioned 15 cm above the water surface. Oxygenation efficiencies of up to 2 kgO2 kW-1 h-1 were observed at low water flow rates. Considering experimental values of power density (DP) and volume of air injected per minute, the vertical tank showed a performance of KLa and EO slightly higher than vertical. The experimental data can be satisfactorily represented by the mathematical models obtained.